A case of three synchronous primary lung cancers within the same lung lobe - Wcisło, Szymon; Misiak, Piotr; Brocki, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
We present the case of a 74-year-old patient with three synchronous primary lung cancers within the same lung lobe. Computed tomography and positron emission tomography investigations revealed two suspicious nodular lesions in the upper lobe of the left lung. Fine-needle aspiration biopsy confirmed that one of the lesions was non-small cell lung cancer. The patient was qualified for surgical treatment, and left upper lobectomy plus lymphadenectomy was performed. Histopathological examination confirmed the presence of three primary cancers in the left lung: keratinizing squamous cell carcinoma, neuroendocrine carcinoma, and acinar adenocarcinoma, localized within the same lung lobe. The patient was classified as having stage T3N1M0 lung cancer (stage IIIA) according to the latest, 7th edition of the TNM classification.